2001
DOI: 10.4049/jimmunol.166.10.6050
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for a Complex Array of Costimulators in the Negative Selection of Autoreactive Thymocytes In Vivo

Abstract: Autoreactive thymocytes can be deleted at an immature stage of their development by Ag-induced apoptosis or negative selection. In addition to Ag, negative selection also requires costimulatory signals from APC. We recently used a fetal thymus organ culture system to show that CD5, CD28, and TNF cooperatively regulate deletion of autoreactive thymocytes. Although these experiments provided strong evidence for the action of several costimulators in negative selection, we wished to demonstrate a role for these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 55 publications
4
32
0
Order By: Relevance
“…To demonstrate that the few transferred MHC molecules could participate in negative selection of T cells, we set up bone marrow chimeras, in which the epithelial-derived MHC would be inefficiently used by DC. We took advantage of the requirement for the CD40 costimulatory molecule in the efficient deletion of Vb5 and Vb6 thymocytes by superantigens [28][29][30]. We therefore compared the extent of negative selection in either MHC II-deficient BM or CD40/MHC II double-deficient BM into B6, AKR or CBA recipients.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate that the few transferred MHC molecules could participate in negative selection of T cells, we set up bone marrow chimeras, in which the epithelial-derived MHC would be inefficiently used by DC. We took advantage of the requirement for the CD40 costimulatory molecule in the efficient deletion of Vb5 and Vb6 thymocytes by superantigens [28][29][30]. We therefore compared the extent of negative selection in either MHC II-deficient BM or CD40/MHC II double-deficient BM into B6, AKR or CBA recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Negative selection of double-positive thymocytes was significantly reduced in response to either Ag or anti-TCR/CD3 Ab in CD28-deficient mice (8). CD28 is also involved in thymocyte negative selection mediated by superantigen both in vitro (9, 10) and in vivo (11). Furthermore, it has been recently reported that prenatal blockade of B7-1 and B7-2 substantially inhibits clonal deletion of T cells in the thymus and leads to an accumulation of autoreactive T cells in the periphery (12).…”
Section: Cd28 Signal Enhances Apoptosis Of Cd8 T Cells After Strong Tmentioning
confidence: 99%
“…7 D and E). The CD40-CD154 pathway is crucial for negative selection of autoreactive thymocytes (31,32). However, WT and CD154 Ϫ/Ϫ thymocytes undergo equivalent and efficient negative selection when they coexist in the thymus of mixed bone marrow chimeric mice, indicating that CD154 signaling is not required specifically on those cells undergoing negative selection (32).…”
Section: Cd154 Is Required Specifically In Developing Foxp3mentioning
confidence: 99%